Analisis Teknikal Sebagai Dasar Pengambilan Keputusan Dalam Transaksi Saham - Wulandari, Putri Amilia (EKALAYA : Jurnal Ekonomi Akuntansi, 2024)
This research aims to study and analyze stock transactions as a basis for decision making in mining industry issuers listed on the Indonesia Stock Exchange. Data was collected through a documentation method using candlestick variables obtained through data analysis on MarketScreener. This analysis uses a candle stick indicator for each company which shows the movement of share price patterns of Mining Industry Issuer companies listed on the BEI and LQ45 for the period 2023. The purpose of this research is to identify the ups and downs in the value of company shares so that errors do not occur in making decisions in stock transactions. The results of the analysis show that nine of the ten mining sector companies that are the subject of the analysis are long-term bearish. term. This can indicate that there is strong selling pressure, so prices tend to fall. It is important to take wise and careful steps in dealing with situations where candlestick analysis shows a decline in prices.